Stakeholders sustainable management in agriculture: lessons from participatory processes - Raposo, Maria Albertina (2019)
Stakeholders are nowadays encouraged to become actively involved in the sustainable management of the territory and, in rural areas such as Castro Verde which is Natura 2000 Special Protection Area and nowadays a UNESCO Biosphere Reserve, as well as in the all country, equilibrium between nature conservation and farm production systems is a key factor for sustainability. This paper focuses on the contribution of local actors to evaluate the agro-environmental commitments applied during the last Portuguese Rural Development Program (PRODER/2007-2013). It aims to propose adjustments and new ideas to improve agricultural sustainable practices by assessing the existing commitments and supporting new public strategies regarding the new 2014-2020 programming cycle of the European Agricultural Fund for Rural Development. This was accomplished through the participation of local stakeholders in a set of five workshops, each one in different agricultural region of Portugal. The three-hour workshops were based on interactive techniques as drivers to generate debate, promote knowledge exchanges and produce new knowledge to be presented to policy makers.